2019
DOI: 10.1158/1078-0432.ccr-19-1700
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Next-Generation Sequencing Unambiguously Distinguishes Separate Primary Lung Carcinomas From Intrapulmonary Metastases: Comparison with Standard Histopathologic Approach

Abstract: Purpose: In patients with >1 non-small cell lung carcinoma (NSCLC), the distinction between separate primary lung carcinomas (SPLCs) and intrapulmonary metastases (IPMs) is a common diagnostic dilemma with critical staging implications. Here, we compared the performance of comprehensive next-generation sequencing (NGS) with standard histopathologic approaches for distinguishing NSCLC clonal relationships in clinical practice.Experimental Design: We queried 4,119 NSCLCs analyzed by 341-468 gene MSK-IMPACT NGS a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 50 publications
1
105
2
Order By: Relevance
“…Unlike conventional small gene panels, large panel next-generation sequencing assys can avoid the limitations of non-information in quite a few cases. A previous study on 76 tumor pairs from sixty patients have shown the utility of the large-scale gene assay (341–468 gene) for assessment of tumor clonal relationships 29 , but Asian populations were unrepresented in this cohort. More recently, the 464 gene panel have been applied to solve the problem of separating MPs from IMs 18 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Unlike conventional small gene panels, large panel next-generation sequencing assys can avoid the limitations of non-information in quite a few cases. A previous study on 76 tumor pairs from sixty patients have shown the utility of the large-scale gene assay (341–468 gene) for assessment of tumor clonal relationships 29 , but Asian populations were unrepresented in this cohort. More recently, the 464 gene panel have been applied to solve the problem of separating MPs from IMs 18 .…”
Section: Discussionmentioning
confidence: 93%
“…Based on the low prevalence of these genes, the odds of coincidental co-occurrence of { EGFR (p.L858R) and ATRX (p.S1012A)} or { EGFR (p.L747_T751del) and RBM10 (p.V467fs)} in two independent tumors were lower than 2.20E − 04 and 3.36E − 04, repectively. Therefore, these two pairs were classified as high-probability IMs 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, NGS screening from 20 to 468 cancer-related genes was applied to identify MPLCs. [52][53][54][55][56][57][58] Seven small studies enrolled a total of 237 patients (range, 11 to 60) and compared the diagnostic efficacy and robustness of the molecular classification with the different histological classifications (Table 2). Overall, NGS provides better discrimination than the clinicopathological classification because it is able to classify more indefinite cases, indicating the importance of NGS.…”
Section: Molecular Characteristicsmentioning
confidence: 99%
“…This study sequencing only 20 genes had no equivocal cases, in part because some indefinite cases sharing only one hotspot driver mutation were classified as IM. 55 In other studies, 53,54,[56][57][58] relationship of 95% of lung adenocarcinomas although the most appropriate detection number of genes remains unknown. Additionally, as shown in Table 2, the molecular classification by NGS conflicts with the histological classification in many cases, and to some extent compensates for the shortcomings of a histological classification.…”
Section: Molecular Characteristicsmentioning
confidence: 99%